2022
DOI: 10.1186/s12871-022-01630-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of single loading dose of dexmedetomidine combined with propofol for deep sedation of endoscopic retrograde cholangiopancreatography (ERCP) in elderly patients: a prospective randomized study

Abstract: Background Endoscopic retrograde cholangiopancreatography (ERCP) is an advanced endoscopic procedure and requires deep sedation. Deep sedation with dexmedetomidine for the respiratory drive preserved has become popular in recent years. However, the use of dexmedetomidine in elderly patients is controversial because its adverse events are more common. The objective of this study was to investigate the effectiveness of a single loading dose of dexmedetomidine combined with propofol for deep sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…Nineteen studies ( Jalowiecki et al, 2005a ; Takimoto et al, 2011 ; Vázquez-Reta et al, 2011 ; Mazanikov et al, 2013 ; Lee et al, 2014 ; Samson et al, 2014 ; Lee et al, 2015 ; Goyal et al, 2016 ; Karanth et al, 2018 ; Kinugasa et al, 2018 ; Nonaka et al, 2018 ; Srivastava et al, 2018 ; Yin et al, 2019 ; Ahmed et al, 2020 ; Koruk et al, 2020 ; Algharabawy et al, 2021 ; Ashikari et al, 2021 ; Aminnejad et al, 2022 ; Chen et al, 2022 ) recorded the risk of hypotension, with 787 patients in the control group vs. 776 patients in the DEX group. There was no significant difference in risk of hypotension between the DEX group (RR: 1.31; 95% CI: 0.85 to 2.02; p = 0.22; I 2 = 61%) and the control group ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies ( Jalowiecki et al, 2005a ; Takimoto et al, 2011 ; Vázquez-Reta et al, 2011 ; Mazanikov et al, 2013 ; Lee et al, 2014 ; Samson et al, 2014 ; Lee et al, 2015 ; Goyal et al, 2016 ; Karanth et al, 2018 ; Kinugasa et al, 2018 ; Nonaka et al, 2018 ; Srivastava et al, 2018 ; Yin et al, 2019 ; Ahmed et al, 2020 ; Koruk et al, 2020 ; Algharabawy et al, 2021 ; Ashikari et al, 2021 ; Aminnejad et al, 2022 ; Chen et al, 2022 ) recorded the risk of hypotension, with 787 patients in the control group vs. 776 patients in the DEX group. There was no significant difference in risk of hypotension between the DEX group (RR: 1.31; 95% CI: 0.85 to 2.02; p = 0.22; I 2 = 61%) and the control group ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (Jalowiecki et al, 2005a;Demiraran et al, 2007;Vázquez-Reta et al, 2011;Koksal et al, 2014;Lee et al, 2014;Samson et al, 2014;Wu et al, 2015;Goyal et al, 2016;Karanth et al, 2018;Kinugasa et al, 2018;Nonaka et al, 2018;Edokpolo et al, 2019;Yin et al, 2019;Ahmed et al, 2020;Algharabawy et al, 2021;Ashikari et al, 2021;Aminnejad et al, 2022;Chen et al, 2022) reported data concerning the risk of bradycardia, which was observed in 721 patients in the control group and 710 patients in the DEX group. There was a significant increase in bradycardia risk in the DEX group (RR: 3.08; 95% CI: 2.12 to 4.48; p < 0.00001; I 2 = 6%) compared with the control group (Figure 5B).…”
Section: Bradycardiamentioning
confidence: 99%
“…Nevertheless, they noted that serious adverse events in elderly patients were rare, and all complications were manageable. The results of Chen et al‘s study [ 26 ] revealed that a combination of dexmedetomidine and propofol for deep sedation in elderly patients candidate for ERCP can reduce sedation-related side effects and provide better hemodynamic conditions compared to propofol alone. Their reported rate of adverse events, including hypoxemia (4.2–36%), hypotension (16.7–60%), bradycardia (12-58.3%), and hypertension (16-20.8%), was higher than that of our study with different anesthesia protocols being possibly a key factor in this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Karakteristik sampel penelitian pada kedua kelompok dapat diketahui bahwa variabel umur dengan hasil median pada kelompok dexmedetomidine 47,4(22-64) dan kelompok fentanyl 44,9(26-64) dengan nilai p = 0,273. Untuk variabel jenis kelamin pada kelompok dexmedetomidine jumlah sampel laki-laki dan perempuan sebanyak 5 (23,8) dan 16 (76,2), sedangkan untuk kelompok fentanyl sebanyak 10 (47,6) dan 11 (52,4) dengan nilai p = 0,197. Berdasarkan hasil tersebut didapatkan bahwa hasil homogen.…”
Section: Karakteristik Sampelunclassified